An integrate analysis of an Hauterivian coral biostrome from the Agrio Formation, Neuquén Basin, west-central Argentina - Garberoglio, Ricardo M. (2013)
A coral biostrome from the lower Hauterivian of the Neuquén Basin, west-central Argentina, was examined in detail. Taxonomic analysis established it as a monospecific assemblage of the scleractinian colonial coral Stereocaenia triboleti (Koby). Palaeoecological analysis of the species allows us to infer that it was an opportunistic species, capable of thriving in mixed carbonatesiliciclatic environments, on a soft substrate under a moderate to low sedimentation rate showing great regenerative capacity. Taphonomic analysis, together with lithofacies and microfacies analysis, allowed us to establish that the coral biostrome was deposited in a middle ramp setting under open marine and well-oxygenated conditions. Corals colonized a soft substrate during a transgressive phase and reaching its climax in the maximum flooding zone under lowest clastic input. They managed to form a low coral meadow of ramose forms of up to 30 cm in height. Coral remains were exposed on the interface after death and thus were subject to severe encrustation and bioerosion. The coral biostrome is interpreted as a mixed biogenic-sedimentologic skeletal concentration deposited by an interplay of an initial biogenic concentration through later episodes of physical reworking, probably storms, which yielded a largely parautochthonous fossil assemblage with minimum lateral transport. As sedimentation rate increased during a highstand interval, the coral-dominated community could not cope with it and was finally buried. The described coral biostrome recorded at the base of a shallowing-upwards cycle closely resembles coral biostromes described from the Hauterivian of Peru and Turkmenistan and differs significantly from framework reef facies recorded in the Hauterivian of the Tethys region from the Paris Basin to Crimea.